2021
DOI: 10.3389/feduc.2021.681258
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Stress: A Psychobiological Approach to Stressful Interactions in the Classroom

Abstract: Teachers report elevated levels of stress and psychosomatic illnesses compared to other professions. Teacher stress has far-reaching consequences on their health outcomes, the student's motivation, and the economy. However, research on teacher stress relies mainly on self-reports, hence, assesses stress on purely subjective perception. Personal or subjective aspects can strongly influence these measures, and biological stress may even be unnoticed. It is, therefore, necessary to include both subjective and obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…We investigated teachers' physiological and self‐reported stress linked to the observed teaching practices in primary school classrooms and to students' learning outcomes in math. The novelty of our study is in combining the effects of both objective and subjective stress indicators on teaching practices and students' learning (see Wettstein et al, 2021). Our results revealed that self‐reported stress is related to teachers' using fewer child‐centred teaching practices compared with teacher‐directed ones, but physiological stress is not associated with teaching practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated teachers' physiological and self‐reported stress linked to the observed teaching practices in primary school classrooms and to students' learning outcomes in math. The novelty of our study is in combining the effects of both objective and subjective stress indicators on teaching practices and students' learning (see Wettstein et al, 2021). Our results revealed that self‐reported stress is related to teachers' using fewer child‐centred teaching practices compared with teacher‐directed ones, but physiological stress is not associated with teaching practices.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers' stress and general well‐being are crucial determinants of the classroom environment, as these are reflected in instructional and classroom management decisions teachers make and, therefore, affect students' learning experiences in the classroom (Jennings & Greenberg, 2009; Roeser et al, 2013; Travers, 2017; Wettstein et al, 2021). We already know that teachers' well‐being is related to their students' math achievement (Klusmann et al, 2016) and that their teaching practices are related to the students' gain in math skills in Grade 1 (Lerkkanen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they have been criticized for being very subjective and sensitive to mood fluctuations. Some researchers have criticized these scales for lack of ability to capture the complexity of stress as they may ignore essential data on real time of physiological stress reactions (Wettstein et al, 2021). Moreover, when responding to these scales, teachers may not report their level of stress accurately, as their self‐evaluation may be affected by their moods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic review of 19 studies reported that school teachers represented an especially high-risk population for mental health disorders during the COVID-19 pandemic [3]. In fact, teachers presented high levels of stress and mental illness compared to other professions [4], since they have to educate many students every day in a closed environment. Indeed, several studies in the literature have shown that more than one third of teachers accumulated high levels of fear of COVID-19 and of serious mental distress during the COVID-19 pandemic [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%